2021
DOI: 10.1016/j.esmoop.2021.100051
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic oral vinorelbine in previously untreated advanced non-small-cell lung cancer patients unfit for platinum-based chemotherapy: results of the randomized phase II Tempo Lung trial

Abstract: Background To assess the efficacy and safety of a metronomic schedule of oral vinorelbine (mVNR) in advanced non-small-cell lung cancer (NSCLC) in patients unfit for platinum-based combination chemotherapy. Patients and methods This was a multicenter, prospective, randomized, open-label phase II study in treatment-naive patients with TNM stage IIIB/IV NSCLC. Patients received mVNR at a fixed dose of 50 mg × 3 or standard schedule 60-80 mg/m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Regarding NSCLC, in our opinion that data are well consolidated in unfit advanced patients [ 78 ], for whom mCHT sometimes can represent the only option of treatment, considering that more aggressive regimens and combinations with immune check inhibitors are precluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding NSCLC, in our opinion that data are well consolidated in unfit advanced patients [ 78 ], for whom mCHT sometimes can represent the only option of treatment, considering that more aggressive regimens and combinations with immune check inhibitors are precluded.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized Phase II Tempo Lung trial, showed that in advanced NSCLC patients unfit for platinum-based first line chemotherapy, metronomic oral VNR at a fixed dose of 50 mg thrice a week significantly prolonged median PFS without grade 4 toxicity compared to standard schedule 60–80 mg/m 2 [ 78 ].…”
Section: Metronomic Chemotherapy: Up To Date In Breast Non-small Cell and Colorectal Cancersmentioning
confidence: 99%
“…Shortly after the small bowel resection, thoracic disease progression was detected by a whole-body CT-scan; thus, the patient stopped immunotherapy (September 2020) and started third-line treatment with oral metronomic vinorelbine (30 mg x3/week continuously) together with a radiotherapy boost (12 Gy total dose). 10…”
Section: Case Reportmentioning
confidence: 99%
“…7 Shortly after the small bowel resection, thoracic disease progression was detected by a whole-body CT-scan; thus, the patient stopped immunotherapy (September 2020) and started third-line treatment with oral metronomic vinorelbine (30 mg x3/week continuously) together with a radiotherapy boost (12 Gy total dose). 10 To date, the patient is still on treatment with metronomic vinorelbine. The scheduled CT-scans have showed stable disease on left chest wall and no abdominal disease recurrence.…”
Section: Case Reportmentioning
confidence: 99%
“…Thus, whereas the former promoted a significant decrease, the latter showed an increase in comparison with the control group [124]. There is some clinical evidence for the efficacy and safety of metronomic vinorelbine in advanced breast cancer and NSCLC [125,126]. Metronomic topotecan with pazopanib showed antitumor activity in murine models of aggressive pediatric solid tumors and a significant reduction in viable blood CEPs and CECs and tumor microvessel density [127].…”
Section: Metronomic Chemotherapy Has a Systemic Antiangiogenic Effect By Reducing Mobilization And Viability Of Bone-marrow-derived Cepsmentioning
confidence: 99%